DEVELOPING CREATIVITY IN THE ART CLASSROOM IN KAZAKHSTANI SCHOOLS: TEACHERS’ BELIEFS, STRATEGIES, BARRIERS, AND ENABLERS - Duissenova, Bakhytzhan (Nаzаrbауеv Unіvеrsіtу Grаduаtе Sсhооl оf Еduсаtіоn, 2023)
Every year the relevance of studying ways to develop creativity in the classroom grows. The study explores art teachers' views on how creativity develops in the classroom. А semi-structured interview was conducted among eight art teachers at Kazakhstani schools as part of the qualitative research. Questions were asked to determine art educators' beliefs on the nature of creativity, strategies, and opportunities that stimulate creative pedagogy in the classroom. Furthermore, the study considered the barriers to developing creativity in art classes...
Master оf Sciences іn Educational Leadership
Keywords: art education; teacher’s beliefs; creativity